1999
DOI: 10.1002/(sici)1098-2353(1999)12:5<382::aid-ca9>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic determinants in the etiology of class III malocclusions: A review

Abstract: Morphospatial disharmony of the craniomaxillary and mandibular complexes may yield apparent mandibular prognathism, but Class III malocclusions can exist with any number of aberrations of the craniofacial complex. Deficient orthocephalization of the cranial base allied with a smaller anterior cranial base component has been implicated in the etiology of Class III malocclusions. Whereas the more acute cranial base angle may affect the articulation of the condyles resulting in their forward displacement, the red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 105 publications
2
41
0
6
Order By: Relevance
“…Space flight studies have established that gravity helps maintain skeletal mass and diminished mechanical forces eliminate signals that maintain osteocyte viability and inhibit bone formation (Aguirre et al, 2006). More importantly, Sinsel et al(1998;1999) revealed that paralysis of the midfacial musculature can result in decreased anterioposterior growth of the snout and nasofrontal sutural growth activity. Actually, mechanical forces play a fundamental role in tissue differentiation and morphogenesis (Radlanski and Renz, 2006).…”
Section: Possible Relationships Between Class III Malocclusion and Pementioning
confidence: 99%
See 1 more Smart Citation
“…Space flight studies have established that gravity helps maintain skeletal mass and diminished mechanical forces eliminate signals that maintain osteocyte viability and inhibit bone formation (Aguirre et al, 2006). More importantly, Sinsel et al(1998;1999) revealed that paralysis of the midfacial musculature can result in decreased anterioposterior growth of the snout and nasofrontal sutural growth activity. Actually, mechanical forces play a fundamental role in tissue differentiation and morphogenesis (Radlanski and Renz, 2006).…”
Section: Possible Relationships Between Class III Malocclusion and Pementioning
confidence: 99%
“…Although the etiology for this malocclusion is complex, the effect of muscular function is highly regarded (Singh, 1999). Concerning the effect of muscular function on the maxillofacial morphology, many scholars (Jung et al, 2003;Takahashi et al, 1999;Thüer et al, 1999) have studied the perioral forces exerted on the mixed and permanent dentition utilizing various techniques.…”
Section: Introductionmentioning
confidence: 99%
“…These phenotypic variations create a significant heterogeneity among Class III subjects that can vary according to sex and ethnicity, and account for some of the difficulty encountered when investigating the condition. (Singh, 1999) The familial nature of mandibular prognathism was first reported by Strohmayer (1937) as noted by Wolff et al (1993) in their analysis of the pedigree of the Hapsburg family. (Wolff et al, 1993) The highest prevalence of Class III malocclusion is observed in East Asian populations such as Korean, Chinese, and Japanese (8%-40%).…”
Section: Class III Malocclusionmentioning
confidence: 93%
“…(Cruz et al, 2008;Downs, 1927 ;El-Gheriani et al, 2003;Krauss et al, 1959;Litton et al, 1970;Niswander, 1975;Stiles & Luke, 1953;Strohmayer, 1937;Thompson & Winter, 1988;Wolff et al, 1993) This contributes to the variety of anatomical changes in the cranial base, maxilla, and mandible that may be associated with "mandibular prognathism" or a Class III malocclusion. (Bui et al, 2006;Singh, 1999) The prevalence of Class III malocclusion varies among races and can show different anatomic characteristics between races. (Ishii et al, 2002) Considering this heterogeneity, and possible epistasis (the interaction between or among gene products on their expression) and even epigenetics, it is not surprising that genetic linkage and candidate gene studies to date have indicated the possible location of genetic loci influencing this trait in several chromosomal locations (see figure 5).…”
Section: Class III Malocclusionmentioning
confidence: 99%
“…Dessa forma, uma mutação deletéria, apesar de produzir um único efeito ao nível molecular, pode resultar em uma síndrome repleta de anomalias morfoló-gicas. A hierarquia reversa também existe, isto é, as características morfológicas geralmente dependem da ação de muitos genes diferentes 16,24 . Em um dos trabalhos clássicos e mais conhecidos a respeito do crescimento e desenvolvimento craniofacial, Moss 14 , em 1975, sugeriu que não havia determinação genética direta para a morfogênese esquelética: o fenótipo seria determinado somente através das matrizes funcionais.…”
Section: A Genética E Os Problemas Craniofaciaisunclassified